Prevalence and Knowledge on Needle Stick Injury among Health care Workers of Tertiary Medical center in India - Kalpana Devi.V; Janani Nandan; Indhumathi K S (ADVANCES IN BASIC MEDICAL SCIENCES, 2026)
OBJECTIVE This study was to assess the prevalence and knowledge of needle stick injury among health care workers, which includes surgeons, emergency room workers, laboratory room professionals, nurses, class 4 workers (cleaners, sweepers, ward boys/helpers, laundry staff, ambulance staff) in a tertiary medical centre in Chennai, Tamil Nadu, India. METHODOLOGY This cross-sectional, questionnaire-based study was conducted among 133 health care workers in ACS Medical College and Hospital over the period of January 2025 to March 2025. Our study includes students and staff of the institution, irrespective of their age and sex, and we excluded HCWs, administrative staff, Trainees or students with less than 6 months of clinical exposure, non-consenting individuals. Data collection was carried out using a standardised questionnaire. Data analysis was carried by Statistical Package for Social Sciences (SPSS) version 22.0. RESULTS Our study showed that class 4 workers, including cleaners, sweepers, ward boys/helpers, laundry staff, ambulance staff (85.7%) had a history of needle stick injury, and the second significant incidence was amongst nurses (60.5%). 74.4% participants had posit4e attitude towards worrying about needle stick injury. 25.5% showed negative attitude towards worrying about needle stick injury. CONCLUSIONS There should be some preventive measures, which include training regarding the safety devices, post-exposure prophylaxis, and regular training for disposal of biomedical waste by the management to elude the occurrence of needle stick injury. Our study has a few limitations, that our self-administered questions could overestimate or underestimate the result.